2015
DOI: 10.21608/ejb.2015.9697
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Broccoli and Ferulic Acid on Imidacloprid-Induced Hepatotoxicity in Rat

Abstract: Imidacloprid may induce oxidative stress leading to generate free radicals and alternate oxygen free radical scavenging enzyme system. This study aims to investigate the hepatoprotective effect of broccoli water extract and ferulic acid on imidacloprid induced oxidative stress and DNA damage in male albino rats. Rats were co-treated with broccoli water extract (200 mg/kg) or ferulic acid (20 mg/kg) with imidacloprid (80 mg/kg) orally for 28 days.The results revealed that imidacloprid induced high serum levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
4
0
2
Order By: Relevance
“…Our findings are consistent with previous studies that confirmed the ability of IMI to induce oxidative damages in various tissues (Duzguner and Erdogan, 2012;Ahmed and Nasr, 2015;Chakroun et al, 2017;El-Sabbagh et al, 2018). Also, several studies suggested the role of oxidative stress in the mechanisms of adverse imidacloprid effects on male and female reproduction (Kapoor et al, 2011;Bal et al, 2012;Lonare et al, 2016) The recorded increase in MDA and H2O2 levels in serum of dams concomitant together with the decrease in GSH content and CAT activity could be attributed to excessive ROS generation induced by maternal exposure to IMI (Kapoor et al, 2010) that may be considered as one of the leading reasons to oxidative stress and lipid peroxidation and hence, oxidative tissue damages of the pregnant dams that may affect their offsprings.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are consistent with previous studies that confirmed the ability of IMI to induce oxidative damages in various tissues (Duzguner and Erdogan, 2012;Ahmed and Nasr, 2015;Chakroun et al, 2017;El-Sabbagh et al, 2018). Also, several studies suggested the role of oxidative stress in the mechanisms of adverse imidacloprid effects on male and female reproduction (Kapoor et al, 2011;Bal et al, 2012;Lonare et al, 2016) The recorded increase in MDA and H2O2 levels in serum of dams concomitant together with the decrease in GSH content and CAT activity could be attributed to excessive ROS generation induced by maternal exposure to IMI (Kapoor et al, 2010) that may be considered as one of the leading reasons to oxidative stress and lipid peroxidation and hence, oxidative tissue damages of the pregnant dams that may affect their offsprings.…”
Section: Discussionsupporting
confidence: 94%
“…Toxic potentials of technical IMI, a neonicotinoid insecticide against mammal’s reproductive function, have been largely documented [5, 6, 25]. Some authors demonstrated that medicinal plants (broccoli) or plant-derived compounds (Ferulic acid or Curcumin ) could be effective in preventing IMI toxicity [12, 13]. Contrary to previous reports which focused on the pure compound, the current study evaluated the reproductive toxicity of colibri®, a commercial formulation made of 3% IMI and the curative potentials of L. acida, an aphrodisiac medicinal plant, in adult male rats.…”
Section: Discussionmentioning
confidence: 99%
“…As oxidative stress tends to be the common feature of many xenobiotic against human systems, extensive research activity has been performed during recent years to find effective and safety solutions, particularly natural compounds with antioxidant properties. In fact, the preventive effect of Broccoli and Curcumin against neurotoxicity and reproductive toxicity respectively of IMI has been reported in rat [12, 13]. However, less is known about the curative potentials of medicinal plants on the reproductive impairments due to IMI.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2015) Japon balığı üzerine uygulamış oldukları organofosforlu böcek ilacı Triazophosun etkilerine bakmış ve sonuç olarak GSH, SOD, CAT ve laktat dehidrogenaz (LDH) aktivitelerinin azaldığını açıklamışlardır (Liu et al, 2015). Ahmet ve Nasr (2015) erkek albino sıçanlar üzerinde uygulamış oldukları brokoli su ekstraktı, ferulik asit ve imidaklopridinin oksidatif stres üzerine sonuçlarını araştırmışlar ve imidaklopridinin, LPO içeriklerini artırdığını, Brokoli ve ferulik asit LPO seviyesini azalttığını, imidaklopridin GSH'yı düşürmüş, brokoli ve ferulik asit birlikte kullanıldığı zaman ise GSH düzeyini iyileştirdiğini açıklamışlardır (Ahmed and Nasr, 2015).…”
Section: Bulgular Ve Tartişmaunclassified
“…Gowri et al (2013) tatlı su balığı Cyprinus carpio üzerine sentetik pretroitlerden sipermetrini uygulamışlar ve 7 gün içerisinde bu kimyasala maruz kalan balıkların DNA ve RNA içeriklerinde değişiklik olmadığı yalnız 14 ve 21 gün süreyle bekletilen balıkların ise DNA ve RNA içeriğinin beyin, solungaçlar ve karaciğerde önemli ölçüde düştüğünü vurgulamışlardır (Gowri, Govindassamy, and Ramalingam, 2013). Ahmet ve Nasr (2015) erkek albino sıçanlar üzerinde uygulamış oldukları brokoli su ekstraktı, ferulik asit ve imidaklopridinin 8-OHdG seviyesini artırdığını ve brokoli ve ferulik asitin kullanıldığı seviyelerde 8-OHdG azaldığını açıklamışlardır (Ahmed and Nasr, 2015). Calviello et al (2006) sıçanlar üzerinde fungusit olan Mancozebi uygulamışlar ve 8-OHdG DNA oksidasyon ve ROS seviyelerinde düşük bir artışın olduğunu ifade etmişlerdir (Calviello et al, 2006).…”
Section: Bulgular Ve Tartişmaunclassified